The regulatory effects of luteolin, calycosin, and formononetin on the NLRP3/IL-33/ILC2s axis in the treatment of allergic rhinitis: mechanistic analysis and therapeutic potential - Jia, Meng; Lei, Xiaochun; Jiang, Fuwei; Li, Detang (Frontiers in Pharmacology, 2025)
Allergic rhinitis (AR), a common IgE-mediated inflammatory condition of the nasal mucosa, presents with nasal itching, episodic sneezing, and runny nose. Emerging evidence indicates that type 2 innate lymphoid cells (ILC2s) are key players in AR development. Epithelial-derived alarmins (IL-33, IL-25, TSLP) activate ILC2s, leading to Th2 cytokine production (IL-4, IL-5, IL-13) that enhances inflammation. Recent research shows that NOD-like receptor protein 3 (NLRP3) can function as a transcriptional regulator of interleukin-33 (IL-33), offering new mechanistic insights into ILC2s dysregulation. Based on analysis and pharmacological validation of various effective components against AR, three compounds—luteolin, calycosin, and formononetin—have been identified as key ingredients due to their notable anti-inflammatory properties. This review systematically explores how these compounds regulate the NLRP3/IL-33/ILC2s signaling pathway, laying the groundwork for developing targeted AR treatments.